COMPARATIVE-MYTHOPOETIC ANALYSIS OF THE IMAGES OF THE QUEEN AND THE PHOENIX - Chinikulov Otabek Saydazimovich (International Journal of Literature and Language Studies, 2026)
This article comparatively examines the genesis, mythopoetic essence, and artistic-philosophical interpretations of the images of Qaqnus in Eastern mythology and the Phoenix in Western mythology. The study analyzes the origins of these legendary birds, their symbolic meanings, and their functional characteristics within literary traditions. Particular attention is paid to the image of Qaqnus in Eastern classical literature, especially in relation to Sufi philosophy, where it symbolizes the concepts of fana (self-annihilation), baqa (eternal existence), spiritual purification, and the attainment of perfection. The article also explores interpretations of the Phoenix as a symbol of rebirth, eternity, cosmic cyclicality, and divine resurrection in Ancient Egyptian, Greco-Roman, and Christian cultures. Furthermore, the archetypal foundations, similarities, and differences of both images are analyzed through the lens of C. G.Jung’s theory of archetypes. The findings demonstrate that Qaqnus and the Phoenix are significant mythological symbols embodying the universal ideas of immortality, renewal, and spiritual elevation in the artistic consciousness of humanity.